Perilaku minum sopi pada remaja di Kupang - Arman Rifat Lette; Atik Tri Ratnawati; Idei Khurnia Swasti (Berita Kedokteran Masyarakat (BKM), 2016)
Sopi drinking behavior among adolescents in KupangPurposeThis research aimed to identify sopi drinking behavior among adolescents in Maulfa.MethodsThis research was a qualitative study with an exploratory design and phenomenological approach. The main informants were adolescents who drink sopi and supporter informants were religious leaders or community leaders, parents, sopi sellers, health workers and adolescents who did not drink sopi. Data collection used observations, In-depth interviews, and focus group discussions. The informant sampling was obtained by purposive sampling through convenience sampling strategy.ResultResults showed that adolescents start to drink sopi since junior high school and senior high school. They have known sopi since the age of 13-17 years old. The number of sopi consumed is usually about two-six bottles and they drink it together with their friends. Some factors that encourage teenagers to consume sopi are: 1) to obtain many friends and build friendship; and 2) to know each other well and to make a good communication between them.ConclusionSocial factors such as a culture play an important role to build the sopi drinking behavior in adolescents. The adolescents consider that sopi drinking behavior is an easy thing to do because it is easy to obtain and cheap.